Microevolution of Neisseria lactamica during nasopharyngeal colonisation induced by controlled human infection. Issue 1 (December 2018) - Pandey, Anish; Cleary, David; Laver, Jay; Gorringe, Andrew; Deasy, Alice; Dale, Adam; Morris, Paul; Didelot, Xavier; Maiden, Martin; Read, Robert
Abstract Neisseria lactamica is a harmless coloniser of the infant respiratory tract, and has a mutually-excluding relationship with the pathogenNeisseria meningitidis . Here we report controlled human infection with genomically-definedN. lactamica and subsequent bacterial microevolution during 26 weeks of colonisation. We find that most mutations that occur during nasopharyngeal carriage are transient indels within repetitive tracts of putative phase-variable loci associated with host-microbe interactions (pgl andlgt ) and iron acquisition (fetA promotor andhpuA ). Recurrent polymorphisms occurred in genes associated with energy metabolism (nuoN, rssA ) and the CRISPR-associatedcas1 . A gene encoding a large hypothetical protein was often mutated in 27% of the subjects. In volunteers who were naturally co-colonised with meningococci, recombination altered allelic identity inN. lactamica to resemble meningococcal alleles, including loci associated with metabolism, outer membrane proteins and immune response activators. Our results suggest that phase variable genes are often mutated during carriage-associated microevolution. Carriage ofNeisseria lactamica, a harmless coloniser of the human respiratory tract, is inversely correlated withNeisseria meningitidis infection. Here, Pandey et al. provide insights into micro-evolutionary processes inN. lactamica during controlled infection of healthy volunteers.